Influence of temperature and different post curing conditions on the mechanical behaviour of polyurethane-based adhesive for civil engineering applications - Abreu Filho, Marco A. (2022)
Sandwich panels based on cold-formed-steel (CFS) face sheets and polyurethane foam (PUR) core were designed and manufactured to be used as a feasible solution for the rehabilitation of degraded floors. This panel is manufactured by a continuous process, whereby the polymerization and foaming of the PUR core is performed simultaneously with the face sheets assembling and their adhesive bonding in certain zones. A three-component polyurethane adhesive, manufactured with the same components as the PUR, is used on the bonding of these steel elements. However, the foaming process of the sandwich panel involves moderate heating at specific stages of its manufacture to enhance polymerization of the PUR, which may influence the adhesive mechanical response. This work intends to establish the best adhesive composition and its thickness to be used on this connection. Additionally, the influence of different curing and post-curing conditions on the shear response of the adhesive is assessed.